2018
DOI: 10.1093/jee/toy064
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Effects of Various Pesticides on Trichogramma achaeae (Hymenoptera: Trichogrammatidae)

Abstract: Little information is available regarding the lethal and sublethal effects of pesticides on Trichogramma achaeae (Nagaraja and Nagarkatti; Hymenoptera: Tricogrammatidae) during integrated management of Tuta absoluta (Meyrick; Lepidoptera: Gelechiidae), an important pest for tomato production. Twenty-two pesticides sprayed on Ephestia kuehniella (Zeller; Lepidoptera: Pyralidae) eggs were evaluated on the mortality of adult parasitoids upon contact with the hosts 24 h after the treatments and their sublethal eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 50 publications
1
28
0
2
Order By: Relevance
“…Therefore, the effects of sublethal doses of pesticides are important for improving IPM programs. In this work, we found that oral ingestion of sublethal doses of IMD, adversely affected parasitoid performance, including the survival rate, parasitic capacity, and longevity of female adults, which was consistent with the performance of the Aphidius colemani, Microplitis mediator, O. insidiosus, C. flavipes , and Trichogramma species exposed to pesticides (D'Avila et al, 2018; Fontes et al, 2018). In the M. mediator , exposure to flonicamid, pymetrozine, spinosad, and thiacloprid reduced its parasitization activity, percentage of parasitism and female longevity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, the effects of sublethal doses of pesticides are important for improving IPM programs. In this work, we found that oral ingestion of sublethal doses of IMD, adversely affected parasitoid performance, including the survival rate, parasitic capacity, and longevity of female adults, which was consistent with the performance of the Aphidius colemani, Microplitis mediator, O. insidiosus, C. flavipes , and Trichogramma species exposed to pesticides (D'Avila et al, 2018; Fontes et al, 2018). In the M. mediator , exposure to flonicamid, pymetrozine, spinosad, and thiacloprid reduced its parasitization activity, percentage of parasitism and female longevity.…”
Section: Discussionsupporting
confidence: 80%
“…In the M. mediator , exposure to flonicamid, pymetrozine, spinosad, and thiacloprid reduced its parasitization activity, percentage of parasitism and female longevity. In addition, IMD impaired the longevity and parasitic capacity of Trichogramma species including Trichogramma achaeae, T. chilonis, T. platneri , and T. pretiosum (Khan and Ruberson, 2017; Fontes et al, 2018). The exposure to pesticides also adversely affected the biocontrol efficiency of pest predators (Moscardini et al, 2013; Nawaz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of deltamethrin on parasitism varies between species of parasitoids 25,26 , but, in general, this insecticide presented low selectivity and high sublethal potential since its low doses can reduce the fecundity and longevity of parasitoids 27 . Deltamethrin reduced the parasitism percentage of Trichogramma brassicae Bezdenko (Hymenoptera: Trichogrammatidae) in Corcyra cephalonica Stainton (Lepidoptera: Pyralidae) eggs to 2.67% 28 and Eretmocerus mundus Mercet (Hymenoptera: Aphelinidae) on Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) nymphs to 30% 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although biological control is essential for Integrated Pest Management (IPM) by maintaining pest populations below economic threshold levels, chemical control in many circumstances is necessary for effective management of stink bugs and other harmful organisms 22 present simultaneously in soybean crops. Therefore, the choice of chemicals for pest control in IPM programs should not be based only on the agronomic efficiency (e.g.…”
Section: Introductionmentioning
confidence: 99%